1987
DOI: 10.1088/0022-3700/20/2/003
|View full text |Cite
|
Sign up to set email alerts
|

Rotational structure in the A-X system of InBr

Abstract: Rotational structure in the A-X system of the indium monobromide molecule has been studied with moderately high resolution. Five bands, namely (2, 0), (1, 0), (0, 0) (0, 1) and (0, 2), were rotationally analysed and rotational constants were determined in the A and the X states for both the isotopic molecules In 79Br and In 81Br. Predissociation has been observed at J=134 in the upsilon =2 level of the A 3 Pi 0 state. This gives an upper limit to the dissociation energy of the InBr molecule of 3.5 eV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 5 publications
2
9
0
Order By: Relevance
“…Randle and Whiffen [19] assigned the symmetric stretching .frequency to a band lying between 1333 and 1370 cm -1 and the antisymmetric frequency between 1494 and 1539 cm-1 in the spectra of aromatic nitrobenzene derivatives. In the present case e have assigned the strong bands at 1355 and 1525 cm-1 (Table H) to ΝO2 symmetric and asymmetric stretching vibrations, respectively, in accordance with the assignments made by Mooney [7], Kishore et al [20] and Singh and Rai [21]. In the Raman spectrum the symmetric vibration has appeared very strongly at 1340 cm-1 but asymmetric vibration has occurred weakly at 1525 cm-1 .…”
Section: Internal Vibrations Of No2 Groupsupporting
confidence: 89%
“…Randle and Whiffen [19] assigned the symmetric stretching .frequency to a band lying between 1333 and 1370 cm -1 and the antisymmetric frequency between 1494 and 1539 cm-1 in the spectra of aromatic nitrobenzene derivatives. In the present case e have assigned the strong bands at 1355 and 1525 cm-1 (Table H) to ΝO2 symmetric and asymmetric stretching vibrations, respectively, in accordance with the assignments made by Mooney [7], Kishore et al [20] and Singh and Rai [21]. In the Raman spectrum the symmetric vibration has appeared very strongly at 1340 cm-1 but asymmetric vibration has occurred weakly at 1525 cm-1 .…”
Section: Internal Vibrations Of No2 Groupsupporting
confidence: 89%
“…The observed wave number of the bands along with their vibrational assignments are listed in tables 2 and 3. The determined constants are in close agreement with the earlier reported values [3,5,8,10]. The comparison between reported values and present study is given in table 1.…”
Section: Resultssupporting
confidence: 92%
“…Nampoori and Patel [4] recorded the spectra on 2 m plane grating spectrograph (PGS-2) at a dispersion of 0.5Å/mm. Vibrational constants reported by Singh et al [5] agree with those of Lakshminarayana and Harnath [3] but their reported values of vibrational heads do not match with each other. They also reported predissociation in A 3 Π 0 state.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The simulation requires vibrationally resolved Franck-Condon factors (F CF ) and transition probabilities A v ′ v ′′ ik as input parameters. F CF of the InBr molecule can be found in literature only for vibrational quantum numbers up to v = 13 [18] and radiative lifetimes can be found only for selected vibrational levels of the A or B state [8]. Therefore F CF and A v ′ v ′′ ik were calculated using the program TraDiMo [19].…”
Section: Franck-condon Factors and Transition Probabilitiesmentioning
confidence: 99%